Manajemen Kolaborasi dalam Meningkatkan Mutu Pendidikan Masyarakat (Studi Deskriptif pada Organisasi Ikatan Keluarga Besar Baringin Sip) - Saparripin Idris; Doharni Rambe; Devi Afriani; Heny Hastuti (Sekolah Tinggi Agama Islam Sumatera Medan, 2021)
This study aims to analyze the various forms of collaborative management (planning, implementation and monitoring) in improving the quality of education carried out by Ikatan keluarga besar Baringin Sip (IKBSS). The method used is qualitative by using a descriptive study approach. Collecting data using observation, interviews, and documentation studies. Data analysis through the stages of data reduction, data verification, and drawing conclusions. Test the validity of the data using triangulation and member check. The results of the research explain that collaboration management is carried out by Ikatan keluarga besar Baringin Sip (IKBSS) organization with formal and non-formal educational institutions in the Baringin village. The collaborative management relates to planning, implementation and monitoring. In terms of planning, IKBSS collaborates in preparing programs and preparing education budgets. In terms of implementation, IKBSS supports directly by being involved in educating and controlling the course of education programs. In terms of supervision by evaluating the achievement of the program and evaluating the realization of the use of the education budget.